Proceedings (87) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Governance and development in West Africa: perspectives for the 21st century is the proceedings of a workshop held from 17-20 June, 1996 in Accra, Ghana edited by Anthony E Ipiki and Joseph K Olayemi 1997 280pp ISBN 1 57360 008 3Winrock...